Assessing Die Filling Using High‐Speed Camera Imaging. Issue 4 (15th February 2018) - Hildebrandt, Claudia; Loerzer, Jost; Gopireddy, Srikanth R.; Urbanetz, Nora
Abstract: The study presents the die filling process of pharmaceutical powders using high‐speed camera imaging. The objectives are to qualitatively visualize and to quantify the powder flow. A model die filling system with a shoe for powder storage and a moving die underneath the shoe was designed. The die filling process is captured through a high‐speed camera and the images allow flow type identification and flow rate calculation. Correlations are generated to predict the fill ratios and flow rates based on particle size data, which could help in process understanding and optimization of die filling. Abstract : Powder flow is visualized through high‐speed camera imaging in a model die filling system. The image analysis allows a qualitative flow type understanding and a quantitative flowability assessment. An approach to correlate easily accessible material properties, such as particle size, with the volume fill rate is presented.